2017
DOI: 10.1267/ahc.16035
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CD4+CD161+ T Cell and Interleukin-10 Expression in Inflammatory Bowel Diseases

Abstract: Mucosal immune dysregulation associated with T cells plays a critical role in the development of inflammatory bowel diseases (IBD). However, the definite significances of these cells in IBD still remain unclear. Therefore, we investigated the population and expression of CD4+CD161+ T cells in the colonic lamina propria mononuclear cells (LPMCs) in patients with IBD by analyses using flow cytometry and immunohistochemistry. Interleukin-10 (IL-10) mRNA levels in both LPMCs and CD4+ T cells in lamina propria (LP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…It is well known that the anti-inflammatory cytokine IL-10 is elevated in colitis patients [47,[82][83][84][85][86]] and our study mirrored this effect upon DSS exposure. Elevated levels of IL-10 could be interpreted as a compensatory mechanism to counteract the substantial inflammation in the colon.…”
Section: Discussionsupporting
confidence: 85%
“…It is well known that the anti-inflammatory cytokine IL-10 is elevated in colitis patients [47,[82][83][84][85][86]] and our study mirrored this effect upon DSS exposure. Elevated levels of IL-10 could be interpreted as a compensatory mechanism to counteract the substantial inflammation in the colon.…”
Section: Discussionsupporting
confidence: 85%
“…IL-10, which was mainly secreted by Treg cells, has been defined as anti-inflammatory cytokine. However, report has also suggested that T cells in UC patients expressed high level of IL-10 in intestine [ 46 , 47 ], and high-level of IL-10 may result in the induction of pro-inflammatory cytokines in IBD [ 47 ]. The increased IL-10 in DSS mice in the present work was consistent with our preceding investigation [ 48 ] and other previous reports [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cleaved caspase-3 (#9664, 1:100 diluted, Cell Signaling Technology) and AFP (N1501, 1:20 diluted, Dako, Glostrup, Denmark), cells were incubated with HRP-conjugated goat anti-rabbit IgG (Dako) for 1 hr and washed with 0.075% Brij/PBS. After visualization with 3-amino-9-ethylcarbazole (Nichirei, Tokyo, Japan), cell nuclei were counterstained with hematoxylin [ 35 ]. As a negative control, normal rabbit IgG (Dako) was used at the same concentration instead of the primary antibodies in each experiment.…”
Section: Methodsmentioning
confidence: 99%